Pengaruh Human Capital, Inovasi, dan Profitabilitas Terhadap Nilai Perusahaan pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2018-2020 - Eveline Nugroho; Rosiyana Dewi (Publikasi Indonesia, 2022)
This study aims to determine the effect of human capital, innovation and profitability on firm value. As for the independent variable, namely human capital is measured using Value-Added Human capital, innovation is measured using the amount of R&D costs divided by total sales and profitability is measured using the Return on Assets ratio to the dependent variable, namely Firm Value as measured by the Price to Book ratio. Values. This study uses a research object of 21 companies with a total of 63 samples from a population of 193 manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The method of determining the sample using purposive sampling. This research was conducted using quantitative methods using secondary data in the form of annual financial statements of companies listed on the IDX during the 2018-2020 period. Hypothesis testing is done by using multiple linear regression method using SPSS 26 software. The results of this study indicate that the independent variable, namely human capital, has a positive effect on the dependent variable, namely firm value and the independent variable, namely profitability, has a positive effect on firm value. However, in this study the independent variable, namely innovation, has no effect on firm value.